Phytochemical analysis of Aglaia macrophylla - Yusof, Khairul Nazri (2013)
The Meliaceae family, comprising of about 1400 species, is an important source of limonoids and tetranortriterpenoids. Aglaia is one of the genus within the family which has been the focus of phytochemical investigations due to its interesting biological activities. Certain species of Aglaia have traditionally been used for their medicinal and healing properties, such as for the treatment of fever, diarrhoea, inflammation and wounds. Although there has been many previous investigations on the genus, thus far, the species A. macrophylla has not been put through any phytochemical investigation. This species is a common species in Peninsular Malaysia. This work describes the phytochemical investigation on the methanolic bark extract of Aglaia macrophylla, leading to the isolation and identification of three new apotirucallane triterpenoids in addition to a known seco-limonoid. All compounds were identified by a combination of spectroscopic methods including UV, IR, 1D and 2D NMR and ESI-MS as well as comparison with literature data. The air-ground barks of Aglaia macrophylla were cold extracted by macerating in MeOH for several hours and repetitive cycles. The concentrated methanolic extract was partitioned into hexane, ethyl acetate and aqueous fractions. The hexane and ethyl acetate fractions were subjected to various chromatographic procedures which included vacuum liquid chromatography (VLC), column chromatography (CC) and finally, repetitive semi-preparative High Performance Liquid Chromatography (HPLC). The bark extract yielded four triterpenoids, one of which is a known seco-protolimonoid with a hemiacetal C-17 side chain, identified as methyl-1,7-diacetoxy-23,24,25-trihydroxy-20,21,24-epoxy-3,4-seco-apotirucall-4(28),14(15)-diene-3-oate (56). The compound is a constituent of another Meliaceae species, Trichilia elegans. The other three compounds (57, 58 and 59) are new, all possessing the same 3-oxoapotirucallane skeleton and carrying highly oxygenated C-17 side chains. The compounds were identified as 3,5,6-trihydroxy-6-methyl-2-(4,4,8,10,13-pentamethyl-3-oxo-1H-cyclopenta[a]phenanthren-17-yl) heptanoic acid (57), 4,4,8,10,13-pentamethyl-17-(23,24,25-trihydroxy-20,21,24-epoxy)-2H-cyclopenta[a]phenanthren-3-one (58) and 4,4,8,10,13-pentamethyl-17-(3,5,6-trihydroxy-6-methylheptan-2-yl)-2H-cyclopenta[a]phenanthren-3-one (59). Compound 58 was obtained from the hexane soluble fraction of the methanolic extract. The side chain was similar to the known 56 except for the loss of the hydroxyl group on C-24. Meanwhile, compounds 57 and 59 were isolated from the ethyl acetate soluble fraction. Compound 59 appears to be the C-21 oxidation product of 57.